Structure and Applications of a Rhamnolipid Surfactant Produced in Soybean Oil Waste - Nitschke, Marcia; Costa, Siddhartha G. V. A. O. [UNESP]; Contiero, Jonas [UNESP] (Humana Press Inc, 2010)
Soybean oil soapstock was utilized as an alternative carbon source for the production of rhamnolipids by Pseudomonas aeruginosa LBI strain. The chemical composition and properties of the rhamnolipid mixture obtained were determined to define its potential applications. The chemical characterization of the rhamnolipid has revealed the presence of ten different homologues. The monorhamnolipid RhaC(10)C(10) and the dirhamnolipid Rha(2)C(10)C(10) were the main components of the mixture that showed predominance of 44% and 29%, respectively, after 144-h of cultivation. The biosurfactant was able to form stable emulsions with several hydrocarbons and showed excellent emulsification for soybean oil and chicken fat (100%). The rhamnolipid removed 67% of crude oil present in sand samples and presented antimicrobial activity against Bacillus cereus and Mucor miehei at 64 mu g/mL and inhibition of Neurospora crassa, Staphylococcus aureus, and Micrococcus luteus at 256 mu g/mL. The results demonstrated that the rhamnolipid produced in soybean oil soapstock can be useful in environmental and food industry applications.
Keywords: Biosurfactants; Rhamnolipids; Soybean oil waste; Soapstock; Pseudomonas aeruginosa